Kinetika Reaksi Pada Sintesis Hidroksiapatit Dengan Metode Presipitasi - Saputra, Fakhri; Fadli, Ahmad; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite is a ceramic material that used in biomedic especially for bone and tooth implant. Hydroxyapatite can be synthesized by precipitation method. The aims of this research is determining reaction kinetic of hydroxyapatite synthesis by precipitation method with variables of temperature and stirring rate. The research was started by dissolving 8,27 grams of CaO in 200 mL of aquadest. Subsequently the dissolution was titrated with phosphoric acid 1,8 M while heated with temperature variation of 40°C, 50°C and 60°C, also stirring rate of 100 rpm, 200 rpm and 300 rpm. Samples were taken in every 20 minutes by 20 mL and aging for 24 hours in freezer. Then sample was filtered by using filter paper, and the filtrate was analyzed by complexometric titration technique. The result shows that the reaction kinetic follows pseudo second order equation and constants of reaction rate increases with increasing temperature following equation of k = 66, 88e- (25819,13 / RT), k = 10,64e- (18812,92 / RT) and k = 167,80e- (24824,77 / RT) for stirring rate of 100 rpm, 200 rpm, and 300 rpm. Constants of reaction rate at 100 rpm is 0,0056 min-1 and increases to 0,0222 min-1 when the stirring speed increased to 300 rpm at 60°C.Key words : ceramic, hydroxyapatite, reaction kinetic, precipitation